Exploring discourses of masculinity within women track athletes' lives in South Africa - Sauzier, Regine Françoise Eva Gabrielle (University of Cape Town, 2023)
This research dissertation explores discourses of masculinity among university-level women track athletes across South Africa. Many scholars have delved into the narratives of racialization and masculinity among black women athletes, muscularity as a premise of athleticism, ‘tomboyism' and gender fluidities, as well as the policing and disciplining of women athletes' bodies in accordance with gender ideals. Nonetheless, as it stands, literature on women's masculinities within sports in South African contexts, along with the idea of meshing masculinities and women's experiences together remains scarce. Interviews were conducted with women sprinters attending universities across South Africa on the online platforms, Microsoft Teams and Zoom, due to the state of the COVID-19 pandemic and restrictions in place at the time. An analysis of their narratives surrounding experiences and discourses of masculinity as cisgendered heterosexual women athletes was carried out. The research concludes that upon reaching adulthood and maturation, the gender binary recloses around the women track athletes so that a "temporary boyhood" is no longer granted to them, and they must negotiate their performative proximity to discourses of masculinity without the safety of the "tomboy" label. Rigid power structures continue to dominate, leaving little to no room for the women track athletes within South Africa to explore a heteronormative female masculinity as part of their gender identities.